Process development studies for the recovery of uranium and sodium sulphate from a low-grade dolostone hosted stratabound type uranium ore deposit. (June 2014) - Suri, A. K.; Sreenivas, T.; Anand Rao, K.; Rajan, K. C.; Srinivas, K.; Singh, A. K.; Shenoy, K. T.; Mishra, T.; Padmanabhan, N. P. H.; Ghosh, S. K.
Abstract : An innovative hydrometallurgical process flowsheet comprising of 'oxidative alkaline pressure leaching–counter-current filtration–direct precipitation–reagent regeneration cum recycle' was developed for effective recovery of the uranium values from a low-grade dolostone hosted stratabound type uranium ore deposit in Southern Cuddapah basin of India. Many challenges inherent in the ore like: lean-tenor (U3 O8 about 0·04%), absence of discrete uranium phases, distribution of majority of uranium values (about 90% by weight) as ultra-fine dissemination in carbonate matrix and presence of reactive sulphide minerals, were converted into opportunities leading to establishment of a process plant after elaborate laboratory and pilot-plant investigations. This paper discusses the results of the laboratory and pilot-plant investigations carried out for development of the process flowsheet.